Religious Freedom and Gender Equality in Modern India with Reference To Śabarimala Temple Case - Prasad, Yellapu; Sridhar, Pininti; Sumitra, S. (Journal of Neonatal Surgery, 2025)
One of the most intense religious disagreements in India is the discussion about the worship of the deity Ayyappa at the Śabarimala temple in Kerala. This article sheds light on the very controversial debate that has been going on for quite some time. In this region, there is a strongly entrenched tradition to prevent women who are fertile from entering the temple. People are believed to be fertile when they are between the ages of ten and fifty. This is due to the fact that this specific temple believes that Ayyappa is a brahmachari, which literally translates to "eternal virgin." Nevertheless, within the same Ayyappa cult in Kerala and some other regions of South India, there exist differences in the representations, interpretations, and rituals of this god. These versions enable women of any age to attend the temples. According to a decision handed down by the Supreme Court of India in September 2018, the prohibition on fertile women discriminated against women. The state of Kerala has been experiencing waves of demonstrations since October 2018, during which supporters and opponents of gender restrictions have battled, sometimes leading to violent altercations. Taking into consideration the Ayyappa cult and the ongoing issues with religious legislation in India, this article investigates the circumstances behind the occurrence of these events. One of the most intense religious disagreements in India is the discussion about the worship of the deity Ayyappa at the Śabarimala temple in Kerala. This article sheds light on the very controversial debate that has been going on for quite some time. In this region, there is a strongly entrenched tradition to prevent women who are fertile from entering the temple. People are believed to be fertile when they are between the ages of ten and fifty. This is due to the fact that this specific temple believes that Ayyappa is a brahmachari, which literally translates to "eternal virgin." Nevertheless, within the same Ayyappa cult in Kerala and some other regions of South India, there exist differences in the representations, interpretations, and rituals of this god. These versions enable women of any age to attend the temples. According to a decision handed down by the Supreme Court of India in September 2018, the prohibition on fertile women discriminated against women. The state of Kerala has been experiencing waves of demonstrations since October 2018, during which supporters and opponents of gender restrictions have battled, sometimes leading to violent altercations. Taking into consideration the Ayyappa cult and the ongoing issues with religious legislation in India, this article investigates the circumstances behind the occurrence of these events.